The hidden architects: nitric oxide and redox dynamics in plant stem cell homeostasis - Zeng, Jian; Zhao, Xin’Ai; Lohmann, Jan U. (Bioessays, 2025)
Plant stem cell homeostasis is a tightly controlled process governed by a complex network of transcription factors, hormones, signaling molecules, and various environmental factors. Among these, nitric oxide (NO) and redox signaling have emerged as critical regulators. This review examines the multifaceted role of NO in maintaining plant stem cell homeostasis, focusing on its influence through redox dynamics, DNA methylation, and hormonal regulation. We also explore the intricate cross-talk between NO signaling and other key pathways, including environmental stimuli and the target of rapamycin (TOR) pathway, in balancing stem cell maintenance and differentiation within both shoot and root meristems. Additionally, we discuss NO's involvement in post-translational modifications and transcriptional regulation, offering insights into its broader role in plant growth and development.